2016
DOI: 10.1111/1753-0407.12480
|View full text |Cite
|
Sign up to set email alerts
|

Association between the vascular endothelial growth factor single nucleotide polymorphisms and diabetic retinopathy risk: A meta‐analysis

Abstract: Background The goal of the study was to reveal the relationship between vascular

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 39 publications
3
18
1
2
Order By: Relevance
“…Several meta‐analyses have been conducted in order to confirm significant associations. VEGFA polymorphisms analysed include −634G > C(rs2010963), +5092C/A (rs2146323), −2578C/A (rs699947), −460T/C (rs833061), +936C/T (rs3025039) and −1154G/A (rs1570360) …”
Section: Vascular Endothelial Growth Factormentioning
confidence: 99%
“…Several meta‐analyses have been conducted in order to confirm significant associations. VEGFA polymorphisms analysed include −634G > C(rs2010963), +5092C/A (rs2146323), −2578C/A (rs699947), −460T/C (rs833061), +936C/T (rs3025039) and −1154G/A (rs1570360) …”
Section: Vascular Endothelial Growth Factormentioning
confidence: 99%
“…VEGF has been found to be the closest gene to SNP in DR-specific gene research [7] . SNP-634C is the most researchful loci.…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether VEGF SNPs are associated with the risk of DR, several meta-analyses have been performed, though the results varied. For example, the study by Xie et al [34] showed that the SNPs rs3025039 and rs833061 were most likely associated with an increased risk of DR. On the other hand, no significant association was found between VEGF 2578C/A polymorphism (rs699947) and DR risk, which was consistent with the results of Gong et al [35]. By contrast, the results from Wang et al [36] supported the association between VEGF 2578C/A polymorphism and the incidence of DR in Asian population, but not in Caucasian population.…”
Section: Association Of Vegf Gene Polymorphisms With Susceptibility Tmentioning
confidence: 99%